Towards Defining the Place and Role of Robotics MOOCs in ODeL - Gouws, Patricia M.; Lotriet, Hugo; Kanakana-Katumba, Mukondeleli G.; Chetty, Denzil (UnisaRxiv, 2021)
This paper focuses on the limited literature pertaining to robotics MOOCs within the STEM MOOC domain. This study provides a subset of an ongoing, more extensive systematic review of the recent advances with MOOCs to advance STEM education and engagement. The purpose of this study is to identify and discuss the place and role of robotics (as a subset of STEM) MOOCs in an open distance e-learning institution of higher education. The study provides insights into the research gaps existing in (1) literature, and (2) the domain of STEM MOOCs for robotics education and STEM engagement. The place and role of STEM MOOCs for the advancement of robotics within an open distance e-learning institution provide a practical and sustainable solution to science engagement in these times of Covid.
Keywords: STEM; MOOC; Robotics education; Science engagement